Analisis Perbandingan Kinerja Keuangan Pada Pt Hanjaya Mandala Sampoerna, Tbk. Dan Pt Gudang Garam, Tbk. Dengan Metode Economic Value Added (Eva) - Lusiana, Erna (Jurnal Manajemen Bisnis dan Kewirausahaan, 2017)
This research aims to find out financial performance of the manufacturing companies which are listed in the Indonesian capital market (Bursa Efek Indonesia) for the period of 2013 until 2015, using Economic Value Added (EVA) method. To get the value of  EVA, data are collected from internet, such as financial statements, stock price, market price and risk free rate. Sample of this research are PT HM Sampoerna, Tbk. and PT Gudang Garam, Tbk. for the period 2013 until 2015. The conclusion of this research is that manufacturing companies which are in miscellaneous sector have a good financial performance and already earn economic value for their stakeholders. Even though companies earn economic value added for their stakeholders, value added of  PT HM Sampoerna, Tbk. keep declining during year 2013 until 2015 caused by the increase of costs, the value of Net Operating Profit After Tax (NOPAT) fluctuated and followed by increasing of cost of capital. Compare to PT HM Sampoerna, Tbk., value added of PT Gudang Garam, Tbk. increasing from year 2013 until 2015. The best financial performance in this research is PT Gudang Garam, Tbk.for it able to increase the value added. Thus, to increase the value added every year for the stakeholders, company of PT HM Sampoerna, Tbk. and PT Gudang Garam, Tbk. have to reduce costs such as production cost, cost of sales, and cost of debts for the profits able to cover all of the costs. Companies also can increasing the volume of sales or work with lower assets to increasing asset turnover.